Comparison of Biparametric and Multiparametric Prostate Magnetic Resonance Imaging in Predicting Oncologic Outcomes After Radical Prostatectomy - Ozgur EFILOGLU; Nesrin GUNDUZ; Ayberk IPLIKCI; Mahmut Bilal DOGAN; Mehmet Caglar CAKICI; Turgay TURAN; Asif YILDIRIM (Medeniyet Medical Journal)
Objective: This study aimed to evaluate the difference in predicting the pathological stage of retropubic radical prostatectomy (RRP) and biochemical recurrence (BCR) in patients with Prostate Imaging Reporting and Data System (PIRADS) scores of 3 and 4 on biparametric prostate magnetic resonance imaging (bpMRI) compared to patients who upgraded from PIRADS 3 to PIRADS 4 based on the contrast-enhanced PIRADS version 2.1. Methods: This study evaluated 107 patients who underwent RRP and had preoperative multiparametric prostate magnetic resonance imaging (mpMRI) and were followed regularly. Group 1 included 31 patients evaluated as PIRADS 3 in both bpMRI and mpMRI, group 2 included 31 patients evaluated as PIRADS 3 in bpMRI and PIRADS 4 in mpMRI, and group 3 included 45 patients evaluated as PIRADS 4 without contrast. Comparisons were made between groups 1 and 2 and between groups 2 and 3. Results: No significant difference was found between the groups in terms of demographic data, preoperative or postoperative radiology, and pathology findings. Extraprostatic extension positivity and BCR were more common in group 2 compared to group 1 although not significant. Multivariate regression analysis was performed to determine the risk factors in predicting BCR, which revealed the positivity of seminal vesicle invasion and high pathological stage in the pathology report as significant factors. Prostate-specific antigen (PSA) and PSA density were higher in group 3 than in group 2, but without significance. Conclusions: This study revealed that mpMRI did not contribute in predicting BCR after RRP compared to bpMRI.